NUEVO NOTHROTHERIINAE (EDENTATA, TARDIGRADA) DE EDAD CHASIQUENSE (MIOCENO TARDÍO) DEL SUR DE LA PROVINCIA DE BUENOS AIRES (ARGENTINA) (Ameghiniana, 2013)
After a study of a mandibular fragment, with two molariforms teeth, coming from the Arroyo Chasicó Formation (Late Miocene) of the southem Buenos Aires Province, we concluded that: a) it is the type of a new taxon, which is named Chasicobradys intermedius n. gen., n. sp.; b) this new Nothrotheriinae is closely related toNeohapalops Kraglievich, 1923 and Senetia Kraglievich, 1925,both from the "Mesopotarnicnsc"(Late Miocene-Pliocene) of the Entre Ríos Province; e) in the Late Miocene of the southem Pampean region the great frequence of Tardigrada sloths is indicative of relatively warm and humid climate, as well as the presence of some forest.